Ex vivo Evaluation of a Liposome-Mediated Antioxidant Delivery System on Markers of Skin Photoaging and Skin Penetration - Min M; Egli C; Bartolome RA; Sivamani RK (Dove Medical Press, 2024)
Mildred Min,1,2 Caitlin Egli,1,3 Rebecca Alonzo Bartolome,4 Raja K Sivamani1,2,5,6 1Integrative Skin Science and Research Sacramento, Sacramento, CA, USA; 2College of Medicine, California Northstate University, Elk Grove, CA, USA; 3College of Medicine, University of St. George's, University Centre, West Indies, Grenada; 4Nalón Innova, Asturias, Spain; 5Department of Dermatology, University of California-Davis, Sacramento, CA, USA; 6Pacific Skin Institute, Sacramento, CA, USACorrespondence: Raja K Sivamani, Integrative Skin Science and Research Sacramento, 1451 River Park Dr. Suite 222, Sacramento, CA, 95815, USA, Tel +1 916-750-2463, Email raja.sivamani.md@gmail.comPurpose: The topical application of antioxidants has been shown to augment the skin's innate antioxidant system and enhance photoprotection. A challenge of topical antioxidant formulation is stability and penetrability. The use of a targeted drug delivery system may improve the bioavailability and delivery of antioxidants. In this ex vivo study, we assessed the effects of the topical application of a liposome-encapsulated antioxidant complex versus a free antioxidant complex alone on skin photoaging parameters and penetrability in human skin explants.Patients and Methods: Human organotypic skin explant cultures (hOSEC) were irradiated to mimic photoaging. The encapsulated antioxidant complex and free antioxidant complex were applied topically onto the irradiated hOSEC daily for 7 days. The two control groups were healthy untreated hOSEC and irradiated hOSEC. Photoprotective efficacy was measured with pro-inflammatory cytokine (IL-6 and IL-8) and matrix metalloproteinase 9 (MMP-9) secretion. Cell viability and metabolic activity were measured via resazurin assay. Tissue damage was evaluated via lactate dehydrogenase (LDH) cytotoxicity assay. Skin penetration of the encapsulated antioxidant complex was assessed via fluorescent dye and confocal microscopy.Results: Compared to healthy skin, irradiated skin experienced increases in IL-6, IL-8 (p < 0.05), and MMP-9 (p < 0.05) secretion. After treatment with the encapsulated antioxidant complex, there was a 39.3% reduction in IL-6 secretion, 49.8% reduction in IL-8 (p < 0.05), and 38.5% reduction in MMP-9 (p < 0.05). After treatment with the free antioxidant complex, there were no significant differences in IL-6, IL-8, or MMP-9 secretion. Neither treatment group experienced significant LDH leakage or reductions in metabolic activity. Liposomes passed through the stratum corneum and into the epidermis.Conclusion: The topical application of a liposome-encapsulated antioxidant complex containing ectoin, astaxanthin-rich microalgae Haematococcus pluvialis extract, and THDA improves penetrability and restored IL-6, IL-8, and MMP-9 levels in irradiated human skin explants, which was not seen in the comparator free antioxidant complex group.Keywords: skin explants, ectoin, astaxanthin, THDA, tetrahexyldecyl ascorbate